Attempts of fusion between the two main companies of a sector: the case of MZA and NORTE - Villacorta Hernández, Miguel Ángel (Hispania Nova, 2019)
The purpose of this investigation is the analysis of the attempts to merge the two largest Spanish private railway companies: NORTE and MZA. The Spanish railway sector has been prolifically studied from various areas, due to the important role it has played in its contribution to economic progress. However, it is necessary to focus on a singular aspect, such as the possibility that the two most important Spanish companies in the sector merged. Although this was not achieved, the procedures are relevant to Spanish business historiography.